2019
DOI: 10.1063/1.5081005
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of the SRP32-vdW specific reaction parameter functional to CHD3 dissociation on Pt(110)-(2 × 1)

Abstract: Stepped transition metal surfaces, including the reconstructed Pt(110)-(2 × 1) surface, can be used to model the effect of line defects on catalysts. We present a combined experimental and theoretical study of CHD 3 dissociation on this surface. Theoretical predictions for the initial sticking coefficients, S 0 , are obtained from ab initio molecular dynamics calculations using the specific reaction parameter (SRP) approach to density functional (DF) theory, while the measured sticking coefficients were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(110 citation statements)
references
References 82 publications
(160 reference statements)
14
95
1
Order By: Relevance
“…We find that the activation barriers for the different surfaces do not depend strictly linearly on the generalized coordination number, as shown in Figure S4, but rather scatter around a line, in reasonable agreement with the trend in adsorption energies of oxygen and hydrogen adsorbates on Pt nanoparticles. 22,23 The geometry of the transition state with the lowest activation barrier, also given in Table 2, more closely resembles that calculated on the stepped Pt(110)-(2 × 1) 33 surface than on the flat Pt(111) 25 surface. Table 2.…”
Section: S Esupporting
confidence: 60%
See 4 more Smart Citations
“…We find that the activation barriers for the different surfaces do not depend strictly linearly on the generalized coordination number, as shown in Figure S4, but rather scatter around a line, in reasonable agreement with the trend in adsorption energies of oxygen and hydrogen adsorbates on Pt nanoparticles. 22,23 The geometry of the transition state with the lowest activation barrier, also given in Table 2, more closely resembles that calculated on the stepped Pt(110)-(2 × 1) 33 surface than on the flat Pt(111) 25 surface. Table 2.…”
Section: S Esupporting
confidence: 60%
“…The Journal of Physical Chemistry C Article Alternatively, the structure of the Pt(210) surface may not be correctly reproduced by the SRP32-vdW functional as functionals which include van der Waals correlation do not necessarily produce the right surface geometry. 64 In recent work on Pt(110)-(2 × 1) 33 we found that the activation barrier for dissociation of CHD 3 was up to 10 kJ/mol higher when the surface structure calculated by using the SRP32-vdW functional was used compared to those obtained experimentally. 65−67 A comparison of the calculated and experimental 63 Pt(210) surface geometries can be found in Table S1.…”
Section: S Ementioning
confidence: 90%
See 3 more Smart Citations